PELEPASAN KONDOM TANPA PERSETUJUAN (STEALTHING): ANALISIS YURIDIS PELANGGARAN OTONOMI SEKSUAL DAN UNSUR KEKERASAN SEKSUAL - Risky Waldo; Tubagus Ahmad Ramadan (Journal of Indonesian Comparative of Syari'ah Law, 2025)
The practice of nonconsensual condom removal or stealthing represents a form of sexual violence that has garnered intensive attention in international legal discourse, yet remains inadequately recognized within the Indonesian legal system. This research aims to analyze the juridical construction of stealthing as a violation of sexual autonomy and evaluate the adequacy of Indonesia's criminal law framework in accommodating such practice. Employing normative legal research methodology with statutory, conceptual, and comparative approaches, this study examines the Sexual Violence Crimes Law, the new Criminal Code, and regulations from various progressive jurisdictions. Research findings indicate that stealthing can be constructed as sexual violence violating sexual and reproductive autonomy through conditional consent theory and reproductive coercion framework. However, normative constructions in existing legislation do not explicitly accommodate this practice, resulting in legal vacuum. This research recommends legislative revision by adding specific provisions regarding stealthing, reformulation of consent concept, strengthening victim protection mechanisms, comprehensive sexuality education, and capacity building for law enforcement officials to provide adequate legal protection for victims.